PENGARUH PERBANDINGAN ALMOND DAN EDAMAME TERHADAP KARAKTERISTIK SUSU ALMOND EDAMAME - Hasanah, Novia; Mayun Permana, I Dewa Gede; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2020)
This research aimed to determine the effect of almond and edamame characteristics against almond edamame milk and to determine the best ratio of almond and edamame to generate the best characteristic almond edamame milk. The experimental design of this research is using Completely Randomized Design (CRD) with five levels of ratio treatment almond and edamame, which are 100%:0%, 90%:10%, 80%:20%, 70%:30%, and 60%:40%. The treatment was repeated three times to obtain 15 experimental units. The obtained data analyzed by variance analysis, and the treatment affecting the observed parameters, the test continue with Duncan test. The result showed that the ratio of almond and edamame had a significant effect in protein content, fat content, total solids, viscosity, pH level, and the scoring test (color, flavor, and taste), but insignificantly on the hedonic test (color, flavor, taste, and overall acceptance) of almond edamame milk. The best almond edamame milk obtained from 60% of almond and 40% of edamame with 6.39% of protein content, 5.57% of fat content, 16.52% of total solid, 246.67 cPs of viscosity, pH 6.57, the sensory test in color (hedonic) was liked, color (scoring) was very greenish-white, in flavor (hedonic) was rather liked, flavor (scoring) was rather typical of edamame, in taste (hedonic) was rather liked, taste (scoring) was rather typical of edamame, and overall acceptance was liked.